2020
DOI: 10.1109/access.2019.2960557
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Multicriteria Optimization Method for Solving the Electric Vehicles Planning Issue in Smart Grids via Green Energy Sources

Abstract: In the given research, a new multicriterion (multiobjective) optimization algorithm has been considered to solve the problem of electric vehicles (EV) scheduling in a smart network in view of sustainable energy sources based on the cost and pollution minimization. By considering the environmental and economic problems, the application of EVs as a proper charging/discharging scheduling model and green energy sources plays an important role in the power system. This study focuses on multicriteria scheduling thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…In [28][29][30], the authors propose modeling mixed vehicular traffic where conventional and unconventional mobility participates; furthermore, it is suggested that multiple charging terminals be considered according to homologation according to the requirements needed by each user. Several variables such as limited capacity, path chance, trip time, flow conservation, charging time, spatio-temporal collaboration, terminal types, and traffic events are considered in [31][32][33], and the main aspects to obtain robust solutions that respond to the different situations where unconventional mobility practices exist are introduced. There are three types of terminals that have a direct relationship with EV charging time.…”
Section: Ev Charging Station Infrastructurementioning
confidence: 99%
“…In [28][29][30], the authors propose modeling mixed vehicular traffic where conventional and unconventional mobility participates; furthermore, it is suggested that multiple charging terminals be considered according to homologation according to the requirements needed by each user. Several variables such as limited capacity, path chance, trip time, flow conservation, charging time, spatio-temporal collaboration, terminal types, and traffic events are considered in [31][32][33], and the main aspects to obtain robust solutions that respond to the different situations where unconventional mobility practices exist are introduced. There are three types of terminals that have a direct relationship with EV charging time.…”
Section: Ev Charging Station Infrastructurementioning
confidence: 99%
“…Differing to traditional vehicles, EVs have the advantages of zero-emission of greenhouse gases (GHGs), such as carbon dioxide, nitrogen oxide, and hydrocarbon, which arise due to the heat generated from the combustion engines. To sustain the community and improve environmental awareness, EVs were invented with higher engine efficiency and minimizing pollutants during driving [9]. For typical EVs, the electricity that is generated from electricity plants and renewable energy sources is stored in EVs' batteries, fuel cells, and ultracapacitors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this way the external information of one agent can affect internal operation of other agents. A multi objective optimization problem for scheduling electric vehicles in smart grids to minimize costs and pollution in a power system from Portugal is formulated in [5]. In the paper, the authors used a multi criteria Cuckoo search to schedule green energy sources and electric vehicles for minimizing the operation and pollution costs.…”
Section: Literature Reviewmentioning
confidence: 99%